05 PEMBERDAYAAN EKONOMI MASYARAKAT DALAM PEMANFAATAN LIMBAH AMPAS TEH SEBAGAI BAHAN BAKU PUPUK BOKASHI (Studi Kasus di Kelompok Wanita Tani Cemara Desa Mattoangin Kecamatan Bantimurung Kabupaten Maros) - Jurnal Agribis; Sulaeman Sulaeman; Arifin Arifin; Mohammad Anwar Sadat (Jurnal Agribis, 2017)
In the evergreen farmer women's group Mattoangin village there is a community economic empowerment activity that aims to utilize and manage tea waste waste into bokashi fertilizer. The purpose of this study was to determine the economic empowerment of the community in the utilization of tea pulp waste as a raw material for bokashi fertilizer in the evergreen women farmer group Mattoangin Village, Maros Regency. This research was carried out in January to June 2017 in Mattoangin Village, Bantimurung District, Maros Regency. This type of research is descriptive qualitative. The results of this study indicate that the economic empowerment of the community in the utilization of tea pulp waste as a raw material for bokashi fertilizer in the evergreen farmer women's group Mattoangin Village, Bantimurung District, Maros Regency is at an average level of empowerment at 95.27%.